Consolidação do diálogo entre Arquivologia, Biblioteconomia, Museologia e Ciência da Informação: a contribuição brasileira - ARAÚJO, Carlos Alberto Avila (2018)
Objective. To present the contributions of the research group based at the School of Information Science, Fed eral University of Minas Gerais, named “Approaches and possible dialogues between Information Science and the areas of Archival Science, Library Science and Museum Studies” to consolidate the problem. Design/Methodology/Approach. We present the dis cussions made from the productions of the members of this group, showing the elements capable of sup porting an epistemological view and the processes of an interdisciplinary dialogue. Results/Discusion. There are several historical, insti tutional and theoretical elements that have the poten tial for dialogue, such as concepts, themes, profession al and educational challenges in each of them. Conclusions. There is some immaturity in the condi tions of dialogue between the three areas, and even more so with the information science. The idea that the foundation is in belonging to the field of social sciences seems to point the way to the realization of possibilities. Originality/Value. The text points to the construction of a reflective space beyond the specificity of each one of the areas, demonstrating the possible dialogues and convergences between them